PENGARUH MEDIA GENIALLY PADA PEMBELAJARAN IPAS TERHADAP MINAT BELAJAR PESERTA DIDIK KELAS IV UPTD SD INPRES OEBA 4 KOTA KUPANG: Penelitian Kuantitatif - Hane, Michaela Yustine; Selly, Jannes Bastian; Ratu, Kurniayu Triastuti R. A (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to test the significant effect of the application of genially media on the learning interest of class IV students of UPTD SD Inpres Oeba 4. This study uses a Pre-experimental research type with a One Group Pretest-Posttest research design. The subjects of the study were all class IV students of UPTD SD Inpres Oeba 4 Kupang City in the 2024/2025 academic year totaling 21 people. Data collection techniques used questionnaires, observation and documentation. The questionnaire data had been tested for validity before being used. Data analysis was carried out using the Paired sample t-test after normality and homogeneity tests were carried out. The results of the study on the hypothesis test using the Paired sample t-test showed a significant level (2-tailed) of 0.000. These results indicate that the significance (2-tailed) 0.00 <0.05, this makes a significant difference in learning interest in the pretest-posttest values. Based on the research results above, it can be concluded that there is a significant influence of genially media on students' learning interest in learning science for class IV UPTD SD Inpres Oeba 4.